2011
DOI: 10.5032/jae.2011.04044
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Bottom Line: How Using Evaluation Results to Enhance Extension Programs can Lead to Greater Levels of Accountability

Abstract: Extension has enhanced the lives of U.S. citizens through adult education in a myriad of ways. However, as budgets get tighter, accountability becomes increasingly more important. Over the years, Extension has reported low level impacts rather than the long-term successes that those working within the system know are occurring. Without enhanced evaluation-driven environments, Extension systems will continue to inadequately report programmatic successes, resulting in a lower perceived public value of Extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Professionals with more experience have perhaps been collecting and using evaluation data for some time and need assistance interpreting and reporting on data they already have, while less experienced individuals need help collecting new information and worry less about what to do with it once in hand. This supports the work of Lamm, Israel, and Harder (2011) who found that extension professionals who valued their own personal use of evaluation data were more likely to conduct in-depth evaluations.…”
Section: Conclusion Recommendations and Implicationssupporting
confidence: 82%
“…Professionals with more experience have perhaps been collecting and using evaluation data for some time and need assistance interpreting and reporting on data they already have, while less experienced individuals need help collecting new information and worry less about what to do with it once in hand. This supports the work of Lamm, Israel, and Harder (2011) who found that extension professionals who valued their own personal use of evaluation data were more likely to conduct in-depth evaluations.…”
Section: Conclusion Recommendations and Implicationssupporting
confidence: 82%
“…Combined with public health data, for example, such an instrument can ensure that a community focuses on existing or accessible resources to address health-related issues such as opioid addiction. From an evaluation perspective, impact data can provide needed insights into the value of programmatic efforts (Lamm et al, 2011).…”
Section: Conclusion Recommendations and Implicationsmentioning
confidence: 99%
“…The Extension Service has established more than a century of unique service valued for objective and unbiased information (Beaulieu & Cordes, 2014;Comer, Campbell, Edwards, & Hillison, 2006). Functioning as a bridge between science and the real-world, Extension's history reflects constructive problem solving and progressive education on research and other university efforts (Hamilton, Chen, Pillemer, & Meador, 2013;Harder, Israel, & Lamm, 2011;Jacob, 2013;Rasmussen, 1989;Rogers, 2003). Despite success in the past, Extension today faces challenges in funding, rapidly advancing technology, changing client needs and demographics, and controversial topics including public policy (Blewett, Keim, Leser, & Jones, 2008;Ladewig & Rohs, 2000;Raison, 2014;Scheer, Harder, & Place, 2011).…”
Section: Introductionmentioning
confidence: 99%